FORM, METHOD AND TOOLS OF TEACHING STUDENTS TO LOGICAL THINKING BASED ON INNOVATIVE EDUCATIONAL TECHNOLOGIES - Sadullayeva Nazokat Kuvondiq qizi (Journals Park Publishing, 2023)
Logical thinking organizes the teaching of students to make decisions and find the necessary information in theoretical and practical difficult situations using the acquired knowledge and skills. All this indicates that the development of logical thinking, if it is not the main task, becomes one of the most important during the student's schooling. In this article, thoughts and comments are made about the forms, methods and means of teaching students to think logically based on innovative educational technologies.
Keywords: Logical thinking, methodology, tools, innovative education, pedagogical technologies, reasoning, mental activity, analysis methodology, audio-visual materials, young people, game methods.